Tren Sea Surface Temperature Pada Monsun Timur di Perairan Indonesia Berdasarkan Data Reanalisis Copernicus Marine - Kusumaningsih, Alvianita Rika Putri; Pitriani, Pitriani; Sukma, Nimaz Tegar (Jurnal Laut Khatulistiwa, 2026)
Sea Surface Temperature (SST) is an important oceanographic parameter that is sensitive to seasonal variability and climate change. Indonesian waters experience strong SST dynamics, particularly during the east monsoon (June–August), which are influenced by monsoonal winds and oceanographic processes such as upwelling. This study aims to examine the variability, anomalies, and long-term trends of SST during the east monsoon in Indonesian waters. The study uses SST reanalysis data from the Copernicus Marine Service for the period 2005–2025 with a spatial resolution of 1/12°. The analysis includes the calculation of annual mean east monsoon (JJA) SST, SST anomalies relative to climatological values, and long-term trends using linear regression and the Mann–Kendall test. The results show that east monsoon SST exhibits interannual variability, with values ranging from approximately 28.1 to 29.3 °C. SST anomalies indicate noticeable year-to-year variations. Trend analysis reveals a statistically significant increase in SST during the east monsoon, with a warming rate of about 0.03–0.04 °C per year. These results indicate that ocean warming continues to occur even during the east monsoon period, which is typically associated with surface cooling. The findings provide important insight into changes in sea surface temperature in Indonesian waters and may support further studies on climate change impacts on marine ecosystems and the management of marine resources.